2016
DOI: 10.1080/14767058.2016.1183640
|View full text |Cite
|
Sign up to set email alerts
|

Is maternal smoking during pregnancy associated with an increased risk of congenital heart defects among offspring? A systematic review and meta-analysis of observational studies

Abstract: Our study presents evidence to support the cardiovascular teratogenic effect of maternal smoking during pregnancy, and their offspring may suffer from approximately a 10% relative increase in the risk of CHDs on average.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 74 publications
(54 reference statements)
2
34
2
Order By: Relevance
“…Consanguinity increases the prevalence of rare genetic congenital abnormalities and nearly doubles the risk for neonatal and childhood death . The use of social drugs such as alcohol and maternal exposure to tobacco smoke are also culpable factors of congenital malformation . Finally, over 90% of severe congenital anomalies are found in low and middle‐income countries where pregnant women often lack access to adequate and quality food…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consanguinity increases the prevalence of rare genetic congenital abnormalities and nearly doubles the risk for neonatal and childhood death . The use of social drugs such as alcohol and maternal exposure to tobacco smoke are also culpable factors of congenital malformation . Finally, over 90% of severe congenital anomalies are found in low and middle‐income countries where pregnant women often lack access to adequate and quality food…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The use of social drugs such as alcohol and maternal exposure to tobacco smoke are also culpable factors of congenital malformation. 22,23 Finally, over 90% of severe congenital anomalies are found in low and middle-income countries where pregnant women often lack access to adequate and quality food. 1,2 Some of the public health measures recommended by the WHO to decrease the frequency of certain birth defects include adequate dietary intake of vitamins and minerals, particularly folic acid in adolescent girls and mothers, preventing maternal exposure to harmful substances, adequate prenatal vaccination, rational prescribing in pregnancy, amongst others.…”
mentioning
confidence: 99%
“…According to a survey, the risk of cleft palate increases by maternal smoking during pregnancy (12), while smoking exposure increases the risk of cleft lip and palate (13). The correlation between maternal smoking and heart failure has been reported in another study; they also reported about 10% relative increase in the risk of suffering congenital heart defects (14). In another survey, maternal smoking was found to be associated with an almost 3 times increased risk of congenital heart defects (OR 2.80; 95% CI 1.76 -4.47) (15).…”
Section: Discussionmentioning
confidence: 83%
“…Nicotine, the potent stimulant present in tobacco, is a neuroteratogen and it is believed to be the most likely cause of cognitive impairment seen in children of smokers (Rogers, 2008). Epidemiologic studies have reported a positive association between maternal smoking during pregnancy and the risk of CHDs (Lee and Lupo, 2013;Sullivan et al, 2015;Zhang et al, 2016). The highest risk was associated with septal and conotruncal defects (Alverson et al, 2011;Lee and Lupo, 2013).…”
Section: Congenital Anomalies Associated With Prenatal Cigarette Smokmentioning
confidence: 99%
“…The highest risk was associated with septal and conotruncal defects (Alverson et al, 2011;Lee and Lupo, 2013). Doseresponse analysis showed increased risk of septal defects, particularly atrial septal defect and ventricular septal defect, with higher maternal cigarette consumption during pregnancy (Alverson et al, 2011;Lee and Lupo, 2013;Zhang et al, 2016). Genetics appears to influence the susceptibility of offspring to maternal smoking-induced CHDs (Tang et al, 2015).…”
Section: Congenital Anomalies Associated With Prenatal Cigarette Smokmentioning
confidence: 99%